Active Immunotherapy for the Prevention of Alzheimer’s and Parkinson’s Disease - Madeline M. Vroom; Jean-Cosme Dodart (Vaccines, 2024)
Neurodegenerative diseases (ND) give rise to significant declines in motor, autonomic, behavioral, and cognitive functions. Of these conditions, Alzheimer’s disease (AD) and Parkinson’s disease (PD) are the most prevalent, impacting over 55 million people worldwide. Given the staggering financial toll on the global economy and their widespread manifestation, NDs represent a critical issue for healthcare systems worldwide. Current treatment options merely seek to provide symptomatic relief or slow the rate of functional decline and remain financially inaccessible to many patients. Indeed, no therapy has yet demonstrated the potential to halt the trajectory of NDs, let alone reverse them. It is now recognized that brain accumulation of pathological variants of AD- or PD-associated proteins (i.e., amyloid-β, Tau, α-synuclein) begins years to decades before the onset of clinical symptoms. Accordingly, there is an urgent need to pursue therapies that prevent the neurodegenerative processes associated with pathological protein aggregation long before a clinical diagnosis can be made. These therapies must be safe, convenient, and affordable to ensure broad coverage in at-risk populations. Based on the need to intervene long before clinical symptoms appear, in this review, we present a rationale for greater investment to support the development of active immunotherapy for the prevention of the two most common NDs based on their safety profile, ability to specifically target pathological proteins, as well as the significantly lower costs associated with manufacturing and distribution, which stands to expand accessibility to millions of people globally.